Detection and investigation of atypical porcine pestivirus in a swine production system - Houston, Grace E.; Jones, Cassandra K.; Woodworth, Jason C.; Palinski, Rachel; Paulk, Chad B.; Petznick, Tom; Gebhardt, Jordan T. (Frontiers in Veterinary Science, 2022)
A commercial farrow-to-finish farm was suspicious of atypical porcine pestivirus (APPV) after observing clinical signs of congenital tremors (CT) and splay leg (SL) of newborn pigs. If introduced onto the farrow-to-finish farm, the two potential routes of introduction were suspected to be through replacement gilts or incoming semen doses. Therefore, this study aimed to determine the incidence of clinical APPV within the sampled population, identify the route of APPV introduction to this system, and determine prevalence of detectable APPV RNA within a population of gilt multiplication farm offspring through an isolation nursery and finisher barn. Farrowing records were analyzed for the presence of CT or SL and corresponding parity of the dam. Overall, incidence of clinically affected litters within batch farrowing groups ranged from 0 to 31% over the course of this investigation. Phylogenetic analysis was conducted on a serum sample from a gilt at the isolation nursery, semen dose for the farrow-to-finish farm, and serum of a CT piglet. Results indicated that the virus circulating in clinically affected piglets was most similar to an incoming semen dose (98.9% nucleotide identity). Blood samples were collected at four time points for the population of animals originating from the gilt multiplication farm and revealed APPV clinical prevalence was 37.5 to 77.5% during the nursery phase and 0 to 26% during the finisher phase. Oral fluids were also collected during the finisher phase and APPV clinical prevalence was 100% for all sampling time points. In summary, introduction of APPV into naïve herds is associated with increased clinical CT and SL cases and is detectable in asymptomatic pigs during the nursery and finisher production phases. This study found that potential screening tests for APPV could include oral fluids or qRT-PCR analysis of semen doses especially when trying to characterize prevalence levels on a naïve farm.